The insertion of the environmental health surveillance in the unified health system - 10.5020/18061230.2012.p3 - Edenilo Baltazar Barreira Filho; José Ricardo Soares Pontes (Revista Brasileira em Promoção da Saúde, 2012)
The integration of environmental monitoring activities in the Unified Health System (SUS) shows some characteristics that differentiate it from the practice of epidemiological surveillance. This occurs mainly because much data on exposure to environmental factors is obtained outside the health sector and the adoption of actions that seek to control and/or prevent requires, in most cases, an intra andintersectoral understanding and articulation, since the health sector is not able, by itself, to provide answers to environmental health issues.In recent years, there has been an increasingly consolidation of the field of environmental health, which includes the area of public health, accustomed to scientific knowledge, to the formulation of public policies and the corresponding interventions (actions) related to the interaction between human health and both natural and anthropic environmental factors, which determine, modulate and influence such interaction, in order to improve the quality of human life from the point of view of sustainability(1).As agreed at the Ist Seminar of the National Environmental Health, held in October 2005 and consolidated in the first National Conference on Environmental Health, held in December 2009, it is understood as an area of intersectoral and interdisciplinarypractice focused on the outcomes, in human health, of ecogeossocialrelations between man and environment(1).Accordingly, the Ministry of Health has been implementing, throughout the country, a Surveillance System in Environmental Health (SINVISA), seeking the improvement of this “model” of activities, establishing expertise into the three levels of government, aiming to consolidate the practice of Environmental Health within the SUS.Normative Instruction No. 1, March 7, 2005, creates SINVISA, establishes the area of action, the scope of the three levels of management within SUS and defines the Environmental Health Surveillance as a set of actions and services provided byagencies and both public and private entities that aim to knowledge and detection or prevention of any change in the environmental determinants and conditioning factors that interfere with human health in order to recommend and adopt measures for prevention and control of risk factors related to diseases and other healthproblems(2).Due to the complexity of the situation, some fields have been identified as fields of action of the Environmental Health Surveillance: monitoring of water quality for human consumption; air quality; monitoring of populations exposed to contaminated soils; chemicals; natural disasters and accidents involving hazardous products; physical factors (ionizing and non ionizing radiation); and working environment(3).There are increasing demands and health problems related to the environment that call for resolution by the state and municipal managers of SUS, which is causing more and more the establishment of partnerships between federal government and agencies and institutions in their respective coverage areas and within the limits of their powers, such as Ministries of Education; Cities; Science and Technology; Labour and Employment; Agriculture; Planning and Management;of Foreign Affairs; Development, Industry and Trade; Social Development and Hunger Alleviation; of National Integration; Transport; Defence; Justice; and Culture(1).Environmental Health Surveillance must be perceived and has been increasingly consolidating its field as an “operative arm” of the health public policy, drawn and strengthened since the Health Sector Reform.As we seek, in our constitution, Article 225, whichsays that everyone is entitled to an ecologically balancedenvironment, a good of common use and essential to ahealthy quality of life, we realize the importance givenby our legislature to the relationship between health andenvironment and, therefore, it is possible to realize thathealth becomes more than just the absence of disease,it is possible to see it as a social and environmentalpractice, where the interdependent relationship betweensociety and the environment is perceived and increasinglystrengthened(4).In this issue of the Brazilian Journal of HealthPromotion, we can find two articles that directly addressquestions related to the Environmental Health Surveillance.In times of publication of the 2914 ordinance, whichestablishes procedures for control and surveillance ofwater quality for human consumption and its potabilitystandards(5), we would like to highlight the articleon “Exposure assessment and risk associated withtrihalomethane compounds in drinking water”. Also, in thisissue, we find the article on the “Environmental Hazard ofpesticides prescribed between the Platinum and Amazonbasins,” in such important moment when the NationalAgency of Sanitary Surveillance reported results of foodanalysis showing pesticides residues(6).Therefore, it is noticed that the magazine has beendistinguishing, ever more, articles that bring up to thescientific debate current and relevant subjects, showing itscommitment to the academic community and continuousenhancement in the scientific scenery of this country.